Estimating the costs of farm-level and district efforts to achieve selenium load targets - Wichelns, Dennis, author; Cone, David, author; Fretwell, Shannon, author; Ward, Kristen, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1998)
Seven irrigation and drainage districts in the California's San Joaquin Valley are participating in a regional program to reduce the load of selenium entering the San Joaquin River. Farmers have improved their irrigation methods to reduce surface runoff and deep percolation, district staff have improved their operations to support farm-level water management efforts, and a regional association has been formed to operate regional drainage facilities and coordinate efforts to achieve monthly and annual selenium load targets. The costs of these efforts include farm-level expenditures for new irrigation systems and for increases in irrigation labor and other water management inputs, district-level expenditures for new facilities and staff to manage water deliveries and drainage water reduction efforts more aggressively, and the fixed and variable costs of operating and maintaining regional drainage facilities. Empirical estimates of these costs for the Broadview Water District in 1997 include $93 per acre for farm-level irrigation improvements, $11 per acre for district-level efforts, and $14 per acre for supporting regional drainage activities.
USCID 14th technical conference
Achieving selenium load targets
Not digitized by CSUL Digital Services.
Presented at Contemporary challenges for irrigation and drainage: proceedings from the USCID 14th technical conference on irrigation, drainage and flood control held on June 3-6, 1998 in Phoenix, Arizona.